Enhanced optical transmission of the triple-layer resonant waveguide structure - Yaremchuk, I.Ya.; Fitio, V.M.; Bobitski, Ya.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
In this paper, we propose and demonstrate a novel guided-mode resonant filter based on a metallic grating sandwiched between two dielectric layers for TE polarization. A theoretical model based on rigorous coupled wave analysis has been developed. The transmission spectra of the grating-based structure show a high transmission band with the corresponding amplitude up to 70% inside the infra-red region. Moreover, the observed optical properties can be exactly tuned by the structural parameters. These properties allow using such structures as compact optical filters, and their spectral characteristics can be easily tuned and scaled.